2005
DOI: 10.1007/bf02430261
|View full text |Cite
|
Sign up to set email alerts
|

Infrared and conductivity studies on blends of PMMA/PEO based polymer electrolytes

Abstract: Abstract. Poly(methylmetacrylate)/poly(ethylene oxide) (PMMA/PEO) based polymer electrolytes were synthesized using the solution cast technique. Four systems of PMMA/PEO blends based polymer electrolytes films were investigated:PMMA/PEO + ethylene carbonate (EC) system, (3) PMMA/PEO + lithium hexafluorophosphate (LiPF6) system and (4) PMMA/PEO + EC + LiPF6 system. The polymer electrolytes films were characterized by Impedance Spectroscopy and Fourier Transform Infrared Spectroscopy (FTIR). The FTIR spectra sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…Figure shows the FTIR transmittance spectra of pure PEO, pure PMMA, PEO/PMMA (90:10) blend, PEO/PMMA/KI/I 2 and PEO/PMMA/KI/I 2 / x wt% of ZnO nanorods fillers. The observed well defined IR vibrational bands of pure PEO spectrum at 1,113, 1,242, 1,280, 1,350, and 1,465 cm −1 are assigned to the COC stretching, a mixed mode of CH 2 twisting, wagging and scissoring, respectively . The vibrational bands of pure PMMA are ascribed to the CO stretching vibration (1,270–990 cm −1 ), CH bending vibration (1,450–1,350 cm −1 ), and CH 2 rocking (810 cm −1 , 750 cm −1 ).…”
Section: Resultsmentioning
confidence: 89%
“…Figure shows the FTIR transmittance spectra of pure PEO, pure PMMA, PEO/PMMA (90:10) blend, PEO/PMMA/KI/I 2 and PEO/PMMA/KI/I 2 / x wt% of ZnO nanorods fillers. The observed well defined IR vibrational bands of pure PEO spectrum at 1,113, 1,242, 1,280, 1,350, and 1,465 cm −1 are assigned to the COC stretching, a mixed mode of CH 2 twisting, wagging and scissoring, respectively . The vibrational bands of pure PMMA are ascribed to the CO stretching vibration (1,270–990 cm −1 ), CH bending vibration (1,450–1,350 cm −1 ), and CH 2 rocking (810 cm −1 , 750 cm −1 ).…”
Section: Resultsmentioning
confidence: 89%
“…In the FTIR spectrum of PEO‐PMMA polymer blend electrolytes, the absorption peaks at 1730 cm −1 are assigned to OCH 3 deformation of PMMA. It can be observed that a new peak at 750 cm −1 may be due to the interaction between the oxygen atom of PEO and carbonyl carbon atoms of PMMA . In the FTIR spectrum of PEO‐PMMA‐KI‐I 2 /2‐MCP, the peak at 1562 cm −1 correspond to the stretching frequency of CNC group of 2‐MCP and it is clear that the intensity of peak is increased with increase in the amount of 2‐MCP.…”
Section: Resultsmentioning
confidence: 93%
“…The miscibility of components is very important for choosing of polymer blends. It is clear from the reported literatures that PEO is miscible in PMMA . PEO is chosen as the electrolyte medium because of its polar and chemically stable nature.…”
Section: Introductionmentioning
confidence: 99%
“…There is also a change in position and intensity for the bands in the 3100-2800 cm À1 region, assigned to the C-H stretching modes, as well as a shift of the band at 989 cm À1 , assigned to the (C-H) deformation mode of O-CH 3 group, to a higher wavenumber value. Once again, all the changes in the spectra are indicative of the presence of interactions between the polymers, mainly involving the methyl group of the PMMA-co-BMA structure [35] . The Raman spectra of the samples are shown in Figure 2, and the main vibrational bands are also reported in Table 1, together with a tentative assignment based on literature [27,28,36,37] .…”
Section: Results and Discussion Vibrational Spectral Studymentioning
confidence: 98%